Virtual Reality and Cognitive-Behavioral Therapy for Driving Anxiety and Aggression in Veterans: A Pilot Study. Issue 2 (May 2018) - Zinzow, Heidi M.; Brooks, Johnell O.; Rosopa, Patrick J.; Jeffirs, Stephanie; Jenkins, Casey; Seeanner, Julia; McKeeman, Alyssa; Hodges, Larry F.
Abstract: Within the U.S. military, motor vehicle accidents (MVAs) are the leading cause of preventable morbidity and mortality. Prior combat exposure and anxiety symptoms are associated with risky and aggressive driving, which is responsible for over half of MVA fatalities. Therefore, interventions are needed to reduce driving anxiety and aggression in veterans in order to mitigate the public health impact of MVAs. Virtual reality exposure therapy (VRET) offers safe, controlled exposure to distressing stimuli. The current study piloted a novel virtual reality and cognitive behavioral intervention (VRET + CBT) for veterans that integrated both anxiety and anger management components. Virtual reality driving scenarios were delivered in a driving simulator and tailored for the military population. Six previously deployed veterans completed eight intervention sessions, as well as pre/post, one month follow-up and six to nine month follow-up assessments. Repeated measures ANOVAs demonstrated significant decline and large effect sizes for PTSD symptoms, driving phobia, hyperarousal in driving situations, anxiety/anger-related thoughts and behaviors, and risky driving. Hyperarousal in driving situations declined by 69%, aggressive driving declined by 29%, and risky driving declined by 21%. Treatment gains were maintained at follow-up. Recruitment, retention, immersion, simulator sickness scores, and qualitative feedback demonstrated feasibility of the intervention. Implications for future research and adaptation are discussed. Highlights: We examined a virtual reality therapy for driving anxiety/aggression in veterans. A transdiagnostic CBT approach integrated anxiety and anger management. PTSD, driving phobia, arousal in driving situations, and risky driving declined. Driving anxiety/anger-related thoughts and behaviors also decreased. Feasibility was supported, and large effect sizes were observed.